Intervention of Orai1 Influences the Response of Nuocytes From Allergic Rhinitis Mice to IL-33. (September 2019) - Lin, Lin; Wei, Jinjin; Chen, Zheng; Tang, Xinyue; Dai, Fei; Sun, Guangbin
Objective: Nuocytes are essential in innate type-2 immunity and contribute to the exacerbation of allergic rhinitis (AR). This study aimed to evaluate the intervention of Orai1 on the response of nuocytes from AR mice to interleukin (IL)-33. Methods: We established a murine model of AR. Nuocytes were obtained from the mouse nasal-associated lymphoid tissue. Then, we assessed expressions of Orai1, Ca 2+ mean fluorescence intensity (MFI) in nuocytes, and their cellular response to mouse recombinant (rm) IL-33. After that, we administered rmlentivirus vectors (lenti) that encoded small hairpin RNA (shRNA) against ORAI1 (lenti-ORAI1) into nuocytes cultures and again evaluated Orai1 and Ca 2+ MFI in nuocytes and their response to rmIL-33. Finally, we adoptively transferred nuocytes alone or nuocytes transfected by lenti or lenti-ORAI1 to AR models to investigate their roles during allergic inflammation. Results: We showed that Orai1 and Ca 2+ MFI were upregulated in AR mice nuocytes. These cells were induced to produce more IL-5 and IL-13 by rmIL-33. However, the intervention of Orai1 by lenti-ORAI1 in nuocytes decreased Orai1 and Ca 2+ MFI and reduced productions of aforementioned cytokines even after the administration of rmIL-33. Numbers of sneezing, nasal rubbing, and counts of eosinophils were all enhanced after the adoptive transfer of nuocytes. Concentrations of IL-5, IL-13, and IL-33 in the nasal lavage fluid (NLF) of allergic mice were also increased. However, the adoptive transfer of nuocytes transfected by lenti-ORAI1 decreased aforementioned parameters. Conclusion: These findings show that the intervention of Orai1 in nuocytes influences the response of nuocytes to rmIL-33.